An investigation of cavitation initiation and length of the two-phase region in a converging-diverging nozzle - Alkotami, Abdulmalik Mohammad (Kansas State University, 2022)
A traditional refrigeration cycle has four main system components which are an evaporator, a compressor, a condenser, and an expansion valve. Different types of refrigerants are used in most cooling cycles. The main objective of this project was to develop a water-based cooling system by investigating the cavitation/flash phenomena for the flow through converging-diverging nozzles. Although, cavitation can be harmful in some engineering applications and causes damage to pumps, refrigeration expansion valves, and capillary tubes, on the other hand, it can be managed and used in a beneficial way. Cavitation in a flowing fluid can cause a reduction in temperature, which can result in energy being absorbed and hence, demonstrating a cooling potential. Cavitation/flash can occur when the static pressure of the fluid falls below the vapor pressure, into a metastable liquid state. This phenomenon has been shown in previous experimental work to occur in water flowing through a converging-diverging nozzle, where the cross-sectional area is constricted at the throat causing the velocity to increase and the pressure to decrease below the saturation pressure. The research presented in this dissertation is focused on developing a complete theoretical model and evaluation techniques to predict the results of the cavitation phenomena in a converging-diverging nozzle. The conservation equations and the laws of thermodynamics are presented to understand the fundamental thermodynamics phenomena and to develop predictive models relevant to the cavitation process. The developed models were used to predict pressure distributions, the onset of flash/cavitation, the condensation shock location, and the length of the two-phase region for water within a converging-diverging nozzle. The predicted results were shown to compare well with the previous experimental work; in particular, with the length of the two-phase region. The length of the two-phase region is defined as the distance from the flash inception point to the location where the condensation shock formed in the diverging section of the nozzle. The length of the two-phase region is also used as a measure for the heat absorption area in the nozzle. The larger the area of heat absorption, the higher the cooling potential is likely to be for the system. Experimental results using water have shown only small temperature drops due to a cavitation process in converging-diverging nozzles, mainly due to the physical properties of water. However, the models developed should also apply to cavitation with other fluids. Hence, this analysis can form the basis for future evaluation and potential optimization of the nozzle geometry, and the identification of alternative fluids (properties), necessary to achieve maximum cooling potential for fluids flowing through converging-diverging nozzles.
Keywords: Cavitation initiation; Length of the two-phase region; Converging-diverging nozzle; Water through nozzle